Assessing the effectiveness of a patient-driven partner notification strategy among pregnant women infected with syphilis in Bolivia. Issue 5 (2nd April 2011) - Díaz Olavarrieta, Claudia; Valencia, Jorge; Wilson, Kate; García, Sandra G; Tinajeros, Freddy; Sanchez, Tahilin
Abstract : Objective: Assess the feasibility and acceptability of a patient-led syphilis partner notification strategy among pregnant women with syphilis, their male partners and treatment completion in Bolivia. Methods: In four provinces, women who had tested positive for syphilis while attending antenatal care visits were recruited to receive a partner notification (PN) intervention on how to notify partners of their positive diagnosis and encourage them to get tested/treated. All women who completed PN counselling and notified their male partners completed self-administered questionnaires regarding PN experiences. Sociodemographic characteristics associated with notification and partner treatment completion were assessed using bivariate and multivariate analyses. Results: 144 women and 137 male partners participated; 78% women notified their partners. No women characteristics were significantly associated with PN. Significantly more male partners (85%) who were notified by women completed syphilis treatment (p<0.05) compared to those notified by providers (66%). In multivariate analysis, men notified by female partners had a threefold greater odds of treatment completion compared to men who had not been notified by partners or by someone else (ie, healthcare worker) (OR 3.45, 95% CI 1.21 to 9.90). 86% of women and 80% of men completed syphilis treatment. Our results suggest that lack of time was considered a barrier to care among men who did not complete treatment. Conclusion: A patient-led partner notification strategy for pregnant women and their male partners appears to be feasible and acceptable, providing evidence for larger-scale effectiveness studies to improve male partner treatment compliance.